2017
DOI: 10.1038/s41598-017-14162-w
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell involvement in glucose tolerance impairment caused by chronic mild stress with sleep disturbance

Abstract: We have developed a chronic mild stress (MS) mouse model by simply rearing mice on a wire net for 3 weeks and investigated the effects of MS on glucose homeostasis and sleep. MS mice showed impaired glucose tolerance and disturbed sleep. One-week treatment with a histamine H1 receptor antagonist (H1RA) ameliorated the glucose intolerance and improved sleep quality in MS mice. MS mice showed an increased number of mast cells in both adipose tissue and the brain. Inhibition of mast cell function ameliorated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Histidine decarboxylase is also found in brain‐resident mast cell and microglia (Iida et al, 2015; Silver et al, 1996). Although recent reports have indicated the involvement of mast cells in sleep–wake cycles and glucose homeostasis (Chikahisa et al, 2017; Chikahisa et al, 2013), and the impact of histamine‐dependent microglial control on depression‐like behaviours (Iida et al, 2017), further studies are required to elucidate the roles of histamine released from mast cells and microglia in brain functions.…”
Section: Histamine Receptors Histidine Decarboxylase and Histamine Nmentioning
confidence: 99%
“…Histidine decarboxylase is also found in brain‐resident mast cell and microglia (Iida et al, 2015; Silver et al, 1996). Although recent reports have indicated the involvement of mast cells in sleep–wake cycles and glucose homeostasis (Chikahisa et al, 2017; Chikahisa et al, 2013), and the impact of histamine‐dependent microglial control on depression‐like behaviours (Iida et al, 2017), further studies are required to elucidate the roles of histamine released from mast cells and microglia in brain functions.…”
Section: Histamine Receptors Histidine Decarboxylase and Histamine Nmentioning
confidence: 99%
“…Mice normally show a strong increase in wake when food deprived, but mice without mast cells lack this response, either due to poor promotion of wake or reduced appetite [41]. In addition, chronic mild stress doubles the number of brain mast cells and increases wake during the active period [42]. Although these observations are intriguing, mice lacking mast cells have normal amounts of wake, NREM, and REM sleep [41], and determining how these cells contribute to normal or pathological sleep/wake behavior will be important directions for future research.…”
Section: Histamine Signaling and Sleep/wake Behaviormentioning
confidence: 99%
“…Several inflammatory conditions are worsened by stress, and mast cell activation with inflammatory mediator release plays a crucial role in stress dependent inflammatory mechanism (Theoharides et al, 2004 ). A recent study showed chronic mild stress for 3 weeks increased the number of mast cells in the brain and disturbed sleep in mice (Chikahisa et al, 2017 ). Interaction between hypothalamus, pituitary, and adrenal gland is an important stress response in neuropsychiatric conditions and depression (Anisman and Merali, 2003 ).…”
Section: Stress Mast Cells and Inflammationmentioning
confidence: 99%